PROFESSIONAL IMPROVEMENT ON THE BASE OF FORMING RESEARCH COMPETENCE IN STUDENTS (Scientific journal of the Fergana State University, 2024)
In this article, the relevance of directing future personnel to scientific research, the components of scientific research competence, and the tasks of higher education institutions in directing students to scientific research were studied and analyzed.